La médiatisation du professeur documentaliste dans l'environnement numérique de travail - Jocelyne Corbin-Ménard (Centre National d'Enseignement à Distance, 2015)
For a few years, secondary school's professionals in France have had to face the generalization of the digital workspaces, and more generally the development of digital technology. This study presents the mediatization activity developed by seven documentalists (professeures documentalistes) using various digital tools. It considers their work situation, characterized by both the confrontation with youthful evolving digital practices and by a working context in which their teaching function is singularly defined by ministerial prescriptions. It points out that despite the existence of a similar structure in each school, practices appear to be very varied. From this absence of normalization the study deduces that the subjects are building a creation space that they invest with their own scenarios. These evince intentions to incite the different categories of users to accomplish certain types of activities. The place of the activity of these professionals in the learning environment, studied according to a systemic approach, questions both their underlying motives and the conditions of the effectiveness of the mediatization process necessary to the development of the autonomy of the pupils.